Effects of chitosan coating with citric acid and potassium sorbate on postharvest decay and browning of longan fruit during cold storage - W. Apai (2018)
The efficacy of chitosan (Cts) in combination with citric acid (CA) and potassium sorbate (PS) on quality retention in the longan was evaluated as an alternative to SO2fumigation. Fresh longan fruits were dipped in solutions of 1.2% Cts + 3.0% CA + 0.3% PS at a pH of 2.8 or 3.3 and compared against those dipped in a solution of 3.0% CA + 0.3% PS at a pH of 2.4. After being dipped, the fruits were air-dried, packed in foam trays wrapped with 11 um thick PVC film and then stored at4 ± 1°C, 90% RH. The non-treated fruit (negative control) and SO2fumigated fruit (positive control) were used as controls. The result revealed that except for SO2fumigation, dipping fruits in Cts + CA + PSata pH of 3.3 significantly delayed pericarp browning. This conclusion was indicated by the lowest browning index and the highest pericarp color values (L*, C* and h○) after 32 days. The delay in pericarp browning for fruits treated with Cts + CA + PS at a pH of 2.8 and fruit treated with CA + PS and the control fruit was 24, 20 and 28 days, respectively. Fruits dipped in Cts + CA + PS at a pH of 3.3 exhibited decreased decay, pericarp pH, weight loss, PPO activity, total phenol loss and retained excellent fruit color and eating quality during cold storage and a subsequent shelf life test at ambient conditions. In contrast, the fruits fumigated with SO2showed the poorest eating quality because of off-odors. Chitosan along with CA + PS (pH 3.3) could well prevent sorbic acid degradation in pericarp of fruits when compared with application of CA + PS alone.